PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR MATERI KONDISI GEOGRAFIS INDONESIA - Purnamasari, Yuli; Pramukawati, Aring (UNIVERSITAS PGRI TULUNGAGUNG, 2024)
This study aims to explore the effectiveness of implementing differentiated learning in grade 5 Social Studies subject, focusing on the topic “Geographical Conditions of Indonesia.” A qualitative method with a case study approach was used in this research, which was conducted at SD Negeri 6 Besole, where students have different geographical backgrounds. Data were collected through observation, interviews, and document analysis. The results show that the implementation of differentiated learning is effective in improving students' participation and understanding. Teachers apply variations in content, process, and learning products that are tailored to students' abilities and learning styles. Students who grasp concepts faster are given additional challenges, while students who need more support get more detailed and simple explanations. Collaborative learning is also implemented, allowing students to learn in groups with support from classmates. This strategy not only improves students' academic understanding, but also helps in the development of social skills, such as cooperation and communication. The results of this study suggest that differentiated learning can be a sustainable learning strategy in social studies subjects, with the potential to create a learning environment that is inclusive and responsive to students' individual needs.